Cabin Fire Risks of Hydrogen-Powered Aircraft: Comparative Analysis and Safety Implications - Nugraha, Wahyu Cakra; Mulyanto, Taufiq; Petit, Jean-François; Jézégou, Joël (Politeknik Penerbangan Indonesia Curug, 2025)
Liquid hydrogen (LH2) is being developed as an alternative aircraft fuel to support the decarbonisation of aviation. Although free of carbon emissions upon combustion, LH2 poses safety challenges, particularly in the confined environment of aircraft cabins. This study aims to identify potential fire hazards due to leakage and use of LH2 through a literature-based comparative analysis of kerosene. The study results show that LH2 has a wide flammability range, low ignition energy, and almost invisible flame, making early detection difficult. Cryogenic properties, explosive potential (BLEVE) and rapid gas dispersion also add to the risk. Therefore, the integration of LH2 in aircraft requires specialised detection systems, adequate cabin ventilation design and updated safety standards to suit the unique characteristics of liquid hydrogen.